A phase 1/2 study of the combination of acalabrutinib and vistusertib in patients with relapsed/refractory B-cell malignancies. Issue 11 (19th September 2021) - Collins, Graham P.; Clevenger, Tracy N.; Burke, Kathleen A.; Yang, Buyue; MacDonald, Alex; Cunningham, David; Fox, Christopher P.; Goy, Andre; Gribben, John; Nowakowski, Grzegorz S.; Roschewski, Mark; Vose, Julie M.; et al.
Abstract: In a phase 1b study of acalabrutinib (a covalent Bruton tyrosine kinase (BTK) inhibitor) in combination with vistusertib (a dual mTORC1/2 inhibitor) in patients with relapsed/refractory diffuse large B-cell lymphoma (DLBCL), multiple ascending doses of the combination as intermittent or continuous schedules of vistusertib were evaluated. The overall response rate was 12% (3/25). The pharmacodynamic (PD) profile for acalabrutinib showed that BTK occupancy in all patients was >95%. In contrast, PD analysis for vistusertib showed variable inhibition of phosphorylated 4EBP1 (p4EBP1) without modulation of AKT phosphorylation (pAKT). The pharmacokinetic (PK)/PD relationship of vistusertib was direct for TORC1 inhibition (p4EBP1) but did not correlate with TORC2 inhibition (pAKT). Cell-of-origin subtyping or next-generation sequencing did not identify a subset of DLBCL patients with clinical benefit; however, circulating tumor DNA dynamics correlated with radiographic response. These data suggest that vistusertib does not modulate targets sufficiently to add to the clinical activity of acalabrutinib monotherapy. Clinicaltrials.gov identifier: NCT03205046.